Foreign direct investment and firm performance: an empirical analysis of Italian firms - Borin, Alessandro; Mancini, Michele (Review of world economics, 2016)
Both empirical and theoretical literature show that multinational firms exhibit a competitive advantage before investing abroad. However, there are no clear empirical results regarding the ex post effects of foreign direct investment (FDI) on firm performance, partially due to the inadequacy of available firm-level data. We build a brand new firm-level dataset able both to represent the extent of Italian firms' foreign activity and to provide reliable measures of key performance indicators, especially total factor productivity (TFP) and employment. We then use a propensity score matching procedure to analyze the causal relationship between FDI and firm performance. Firms investing abroad for the very first time, especially in advanced economies, show higher productivity and employment dynamics in the years following the investment: the average positive effect on TFP is driven by new multinationals operating in specialized and high-tech sectors, while the positive employment gains are explained by an increase of the white collar component. On average there are no negative effects on the parent firm's blue collar component.